PENGARUH DISIPLIN KERJA DAN PROSEDUR KERJA TERHADAP KINERJA KARYAWAN MELALUI PRODUKTIVITAS KERJA PADA PT BUMI SUBUR 4 PANARUKAN SITUBONDO - Endayani, Novi; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of the study was to determine the effect of work discipline and work procedures on employee performance through work productivity at PT Bumi Subur 4 Panarukan Situbondo. The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results showed that work discipline had a positive but not significant effect on work productivity. Work procedures have a positive and significant effect on work productivity. Work discipline has a positive and significant effect on employee performance. Work procedures have a positive and significant effect on employee performance. Work productivity has a negative and insignificant effect on employee performance. Work discipline has a negative and insignificant effect on employee performance through work productivity. Work procedures have a negative but significant effect on employee performance through work productivity